Comparison between the radial forearm and superficial circumflex iliac artery perforator free flaps for oral soft tissue reconstruction. Issue 2 (February 2023) - Hurrell, M.J.L.; Clark, J.R.; Ch'ng, S.; (Hubert) Low, T.-H.; Nguyen, K.M.; Elliott, M.S.; Palme, C.E.; Wykes, J.
Abstract: The radial forearm free flap (RFFF) is widely used for oral reconstruction. The superficial circumflex iliac artery perforator (SCIP) flap is an increasingly utilized alternative. The cases of 165 patients who received either an RFFF or SCIP flap for oral reconstruction at Chris O′Brien Lifehouse, Sydney were reviewed. The aim was to report on patient, pathology, treatment, and outcome variables and to compare these between the two flap groups. A RFFF was used in 126 patients and a SCIP flap in 39 patients. SCIP flap patients were younger ( P < 0.001) and had shorter operative times ( P < 0.001), shorter anaesthetic times ( P < 0.001), and more frequent recipient site dehiscence ( P = 0.005) when compared to RFFF patients. The SCIP flap was significantly less frequently used for composite resections including bone when compared to the RFFF ( P < 0.001). The primary site distribution was more even for RFFF patients ( P < 0.001). There were no SCIP flap failures; three RFFF failures occurred. SCIP flaps performed comparably in terms of operative and clinical outcomes. Most SCIP flaps were utilized in younger patients with partial glossectomy defects.